Modelling kinetics of watercress (Nasturtium officinale) colour changes due to heat and thermosonication treatments - Cruz, R. M. S. (2013)
Watercress (Nasturtium officinale) colour changes due to blanching by heat and a combined treatment of heat/ultrasound (thermosonication) were studied in thetemperature range of 82.5 to 92.5 °C. The application of thermosonication was intended to enable less severe blanching treatments and, therefore, improve the quality of the blanched product. The thermosonication blanching processes promoted changes of the green colour (an parameter) at a higher rate (P < 0.05), when compared with the heat blanching processes. No significant differences (P > 0.05) were detected between heat and thermosonication blanching processes in terms of the colour parameters Ln, bn and TCD changes.In both treatments, a fractional first order model fitted well the experimental data for Ln, an and bn (RH2 = 0.99; RTs2 = 0.99) and TCD (RH2 = 0.92; RTs2 = 0.96) colour parameters. The chlorophylls content showed no significant differences (P > 0.05) between thermally treated and thermosonicated watercress samples. The present findings will help to evaluate the effectiveness of thermosonication as a novel process to replace the classical heat treatment.